LITERASI MEDIA ANAK USIA DINI: STRATEGI PENANGGULANGAN KEKERASAN SEKSUAL PADA ANAK - Endah Silawati; Charlotte Ambat Harun; Winti Ananthia; Desiani Natalina Muliasari; Yeni Yuniarti; Margaretha Sri Yuliariatiningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Media literacy for children is important and crucial issue in digital era since it influences children’s development. Some findings show that some sexual abuse cases happened because most of the people are media illiterate, specifically the predator, the victims and people around the victims. Unfortunately, study on media literacy for children in the context of Indonesia is limited. Thus, the article will describe the literatures of learning strategies that assumed effective in developing media literacy of the children. This study is part of ongoing project entitled,” Program Pengembangan Model Desa Ramah Anak Anti Kekerasan Seksual Melalui Pembentukan “Komunitas Sayang Anak” oleh Posdaya Terintegrasi dengan BKB dan BKR Desa.” The literature review method was employed in this study to review and analyze some theories andconcepts related to the program. Data analysis was conducted to categorize the themes that suitable and applicable for the children. The data showed that media literacy development of the children should focus on some aspects, and those are: (1) parental guidance, (2) children’s critical thinking skills, and (3) kinds of media. The development of each aspect should be developed based onthe children’s developmental stages and learning styles.          Keywords: media literacy of children, early childhood education, sexual abuse of children.